AUDİT DİMENSİON OF CORRUPTİON AND ETHİCS PROBLEMS THAT LOCAL GOVERMENT FACED (Third Sector Social Economic Review, 2014)
Today, the central and local governments all over the world are on the agenda for the new management approaches. New public administration and governance are shaping these processes. In particular, governance principles has been extensively used in order to ensure effectiveness and efficiency in the the management system. To be effective and efficient ofg local governments is very important in terms of the public to the nearest service generating units. Today, the effectiveness of local governments, especially the increase in uncontrollable behaviors influence is very fallen. This is a direct negative impact on the standard of living of the people. In this study, from the perspective of governance, how unethical behaviorprevented in local governments will be discussed. Governance principles,, especially accountability, openness, transparency and accountability can shape the audit process in local governments. Organizations carrying out the audit in this area, can implement the principles by checking applications. In the study to support of this thesis, before the conceptual framework of the local governments will be determined then examined the problems of corruption in local government. Where unethical behavior within the scope of these problems will be investigated.After corruption structural and operational issues have been addressed in two context what can be done to prevent unethical behavior in local government questioned.In this direction due to the restructuring of Turkey's audit units will be highlighted.
Keywords: Local Government; Ethics; Corruption; Audit; Efficiency